EFFECT OF CULTURE MEDIA ON GROWTH AND SPORULATION OF Colletotrichum lindemuthianum (SACC AND MAGN) ISOLATES CAUSING ANTHRACNOSE OF FIELD BEAN - S. NARASIMHA RAO* , S.L. BHATTIPROLU AND V. PRASANNA KUMARI, (The Journal of Research ANGRAU, 2024)
Anthracnose (Colletotrichum lindemuthianum) is the most important fungal disease affecting field bean. Growth and sporulation of thirty six isolates of C. lindemuthianum collected from five agro-climatic zones of Andhra Pradesh was evaluated in the year 2017-18 on four different solid and liquid culture media. Results revealed that potato dextrose agar was the best for both radial growth (66.74 mm) and dry mycelial weight (264.74 mg), whereas, host leaf extract agar significantly supported more sporulation 7.3 x104. The least mycelia growth of 39.32 mm, dry mycelial weight of 234.70 mg and sporulation 2.9 x104 were observed on Sabourband’s agar. Among the different isolates, Cl-33 grew fast with mycelial growth and sporulation (78.86 mm and 8.4x104) and Cl-32 produced the highest dry mycelial weight 266.75 mg). The least radial growth (31.35 mm), the lowest sporulation (4.1 x104) and lowest mycelial dry weight (227.75 mg) was recorded in CI-28, CI-1 and CI 17, respectively. Mean conidial length of 36 isolates ranged from 11.87 to 13.03 µm with the maximum length (13.03 µm) recorded in host leaf extract agar, while minimum was recorded in oat meal agar. Width of conidia varied from 3.59 to 4.11 µm on different media and 3.53 to 4.23 µm in different isolates.The growth phase study revealed that increase in the dry mycelial weight of fungus upto 15 days of incubation and growth declined from 17th day onwards.